2015
DOI: 10.1016/j.jclepro.2014.01.083
|View full text |Cite
|
Sign up to set email alerts
|

Improving the CO2 performance of cement, part I: utilizing life-cycle assessment and key performance indicators to assess development within the cement industry

Abstract: Improving the CO2 performance of cement, part I: Utilizing life-cycle assessment and key performance indicators to assess development within the cement industry, 2015, Journal of Cleaner Production, (98) AbstractCement is a vital and commonly used construction material that requires large amounts of resources and the manufacture of which causes significant environmental impact. However, there are many different types of cement products, roughly ranging from traditional products with rather linear resource flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(74 citation statements)
references
References 33 publications
3
71
0
Order By: Relevance
“…National pozzolan was derived from volcanic glass, zeolitic trass, rice husk ash and diatomaceous earth. The use of pozzolan was considered to substitute the amount of clinker consumption in the range of 10 − 75% [6], [14][15]. In scenario 3, it is important to note that the input amounts of raw material and energy used were linearly decreased in proportion to the amount of the additional of natural pozzolan in the clinker substitution rate from 19 to 29%.…”
Section: Inventory Results Of Blended Cement (Scenario 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…National pozzolan was derived from volcanic glass, zeolitic trass, rice husk ash and diatomaceous earth. The use of pozzolan was considered to substitute the amount of clinker consumption in the range of 10 − 75% [6], [14][15]. In scenario 3, it is important to note that the input amounts of raw material and energy used were linearly decreased in proportion to the amount of the additional of natural pozzolan in the clinker substitution rate from 19 to 29%.…”
Section: Inventory Results Of Blended Cement (Scenario 3)mentioning
confidence: 99%
“…The recycling of CKD exhibited the insignificant environmental saving over the traditional process. Feiz et al [15] examined the global warming potential (GWP) impact of five different clinker substitutions at rate of 0% (conventional process), 10%, 53%, 60, and 75% in cement manufacturing. Their results indicated that the clinker substitution rate significantly effects on the environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…This research used water withdrawals relative to renewable water resources to determine water stress; however, in considering mitigation strategies, changes in consumption and withdrawal are examined as they have different implications for water systems. Although electricity demand is often not considered a major factor of the GHG emissions from concrete 35 , the expected high water consumption values for electricity in this sector drives improvements that can potentially reduce water consumption for concrete production. For example, if electricity is generated using wind power, water consumption for the production of concrete could decrease by 25%, and water withdrawal could decrease by 46% (Fig.…”
Section: Mitigation Strategies and Data Qualitymentioning
confidence: 99%
“…This paper is the third in a series of three, all of which are included in this special issue. The first introduces cement production and the selected case, and includes information about the LCA-based methodology (Feiz et al, 2013a) 3 . It provides results from a comparison of different cement products and production systems.…”
Section: Introductionmentioning
confidence: 99%